Cost-Effectiveness of Hearing Screening in Older Adults: A Scoping Review. (February 2022) - Hsu, Amber K.; Bassett, Sarah M.; O'Dwyer, Linda C.; McHugh, Megan; Heinemann, Allen W.; Jordan, Neil; Dhar, Sumitrajit
Objectives: Age is the most common predictor of hearing loss; however, many older adults are not screened. Hearing screening could improve healthcare access, participation, and outcomes. Establishing whether hearing screening in older adults is cost-effective could improve the availability and utilization of screening. Methods: We searched nine databases in January 2020. Studies with populations aged 50+ and provided data on the cost-effectiveness of hearing screening were included in the review. Results: Five studies met the inclusion criteria and all found hearing screening programs to be cost-effective compared to no hearing screening, regardless of screening method (i.e., instrument or strategy). The maximum number of repeated screenings, coupled with younger ages, was most cost-effective. Discussion: This review suggests that hearing screening in older adults is cost-effective, however, the evidence is limited. There is pressing need for research focused on economic impacts of hearing healthcare in older adults to inform research, policy and practice.